The political economy of "local foods" in Eastern Kansas - Champion, B; Benjamin L. Champion (2007)
Alternative agriculture and counter-cuisine movements have grown to a strong cultural current in Western European and North American societies. In recent years,these movements have begun to converge and coalesce around the concept of localizing agri-food relations and commodity chains as a way of redressing the deleterious environmental, social, and economic consequences of what are seen as dominant globalized food relations. This dissertation reports on a regional study in Eastern Kansas of the political economy of local food relations that has arisen through this producer and consumer response. It is an effort to recognize the regional interplay of disparate forces in constructing local food systems in the interest of framing more contextualized and nuanced questions about the environmental, social, and economic outcomes of alternative agri-food development. Network, conventions, and spatial analysis theories and methods were customized and put into practice in the service of these aims, using triangulation among them to mitigate each of their individual weaknesses in representing the variable embeddedness, politics, and spaces of local food in Eastern Kansas. It was found that local food generally represents a marketing niche in urban consumerism that is served primarily by regional rural producers. The distances, agricultural and food ecologies, forms of organization, and values underpinning local food linkages were all found to vary quite considerably throughout the region, creating a diverse combination of development agendas and impacts from local food networks and making food localization a highly contested concept. Local food development in its current form is thus highly dependent on urban/rural dialectics and projects of urbanization that lack open, transparent, and reflexive governance. Critical acknowledgement of these development interdependencies is important as a step toward encouraging social, economic, and environmental justice through local food development.